2013
DOI: 10.4025/cienccuidsaude.v12i3.18903
|View full text |Cite
|
Sign up to set email alerts
|

<b>Vivências de gestantes soropositivas em relação à assistência de enfermagem: estudo descritivo</b> DOI: 10.4025/cienccuidsaude.v12i3.18903

Abstract: RESUMOO objetivo do estudo consistiu em descrever a vivência das gestantes portadoras do vírus da imunodeficiência humana (HIV) e a assistência de enfermagem recebida no pré-natal sob a ótica da gestante. Estudo do tipo descritivo-exploratório, de abordagem qualitativa, cujos sujeitos foram oito gestantes portadoras do HIV, atendidas no Hospital Universitário Antônio Pedro em 2008. A coleta de dados ocorreu através de entrevista semiestruturada, na análise dos dados utilizou-se a análise de conteúdo de Bardin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, despite this support in the ANC some women in this study stated that they still faced negative attitudes from some health care providers and did not want to share their story too much. This 'mixed-picture' is also reflected in the literature -studies still reveal women with HIV describing negative attitudes and poor care in the ANC environment (Viana et al, 2013). Kelly et al (2013) found that the key ANC staff can have significant positive and negative impacts on the experiences of HIV positive pregnant women; empathy and understanding of their unique needs and continuity of care fostered a good experience for example whilst lack of communication, lack of knowledge and experience of HIV care contributed to negative experiences (Gogna et al, 2009).…”
Section: Hiv Disclosure 'Control and Out Of Control'mentioning
confidence: 96%
See 1 more Smart Citation
“…However, despite this support in the ANC some women in this study stated that they still faced negative attitudes from some health care providers and did not want to share their story too much. This 'mixed-picture' is also reflected in the literature -studies still reveal women with HIV describing negative attitudes and poor care in the ANC environment (Viana et al, 2013). Kelly et al (2013) found that the key ANC staff can have significant positive and negative impacts on the experiences of HIV positive pregnant women; empathy and understanding of their unique needs and continuity of care fostered a good experience for example whilst lack of communication, lack of knowledge and experience of HIV care contributed to negative experiences (Gogna et al, 2009).…”
Section: Hiv Disclosure 'Control and Out Of Control'mentioning
confidence: 96%
“…Nurses were significantly more prejudiced and less willing to care for women who were HIV positive than those who were not. While Viana et al (2013) found the role of nurses in the patient's view was confused with other nursing professionals and sometimes women resented not receiving more specialised nursing care. This view is supported by the study conducted by Kelly et al (2013) who found that the key positive staff attributes that facilitated a positive patient experience were knowledge and experience, empathy, and understanding of their unique needs and continuity of care.…”
Section: Theme 6: Interaction With Health Care Providers/ Health Care...mentioning
confidence: 99%
“…Care is not summed up in an act, but in attitudes that involve more than a period of attention, zeal and devotion. It represents feelings of concern, responsibility and affective involvement with the other (VIANA et al, 2013).…”
Section: Nursing Carementioning
confidence: 99%